Word-of-mouth communication and opinion leadership - Kimmel, Allan J. (Henry Stewart Talks, 2013)
The power of consumer-to-consumer influence, Case examples: Hush Puppies; The Hunger Games, Defining word of mouth (WOM), Online vs. offline WOM, Customer reviews, What consumers are talking about and to whom, Consumer influencers, Opinion leadership process, Means to identify influencers, Converting consumers into advocates, WOM motivations
Reviewed at 2018/09/27